Two Dimensional Tunable Optical-CDMA System - Rajesh Yadav Yadav; Gurjit Kaur Kaur (Institute of Advanced Engineering and Science, 2016)
In this work an experimental demonstration is proposed to implement the synchronous optical code division multiple access system using two dimensional wavelength hopping and time spreading optical prime code is presented. An optical CDMA system is configured on latest version of optisystem by optiwave for the 20 users (Prime Number = 5) connected in a network operating at a bit rate 10 Gbps each. Tunability is achieved by using a MATLAB based delay selector which serves as the source of control signal for optical delay lines. The encoded optical signal of each user has been assigned a particular mode. The resulting optical signal is then transmitted over parabolic index multimode optical fiber. The received signal can successfully be retrieved at the decoder, when the encoder and decoder are configured for the same user. The performance of Optical CDMA system is evaluated in terms of the autocorrelation and cross correlation function, BER, Q factor, eye diagram and compared with 1D code for a given prime number.